(untitled) (Swiss Medical Weekly, 2026)
BACKGROUND: Systolic blood pressure is a prognostic marker in acute heart failure, but the prognostic implications of in-hospital changes in systolic blood pressure are unclear. We assessed the association between in-hospital systolic blood pressure changes and outcomes in a real-world, multinational cohort of acute heart failure patients. METHODS: We analysed consecutive patients hospitalised for acute heart failure between 2005 and 2020 at two tertiary-care centres (CHUV, Switzerland; NCCIM, Kyrgyzstan) with available systolic blood pressure measurements at admission and discharge. Patients were classified into four systolic blood pressure trajectory categories: stable normal/low (systolic blood pressure consistently <140 mm Hg or minor increase, Δ<10), increasing (systolic blood pressure rose ≥10 mm Hg from <140 to ≥140 mm Hg), decreasing (systolic blood pressure dropped ≥10 mm Hg from ≥140 to <140 mm Hg), stable elevated (systolic blood pressure consistently ≥140 mm Hg or minor decrease, Δ<10). The primary outcome of the study was a composite of first heart failure hospitalisation or all-cause mortality, assessed over a 1-year follow-up period. The association between categories and the primary outcome was assessed with Cox models, adjusted for relevant covariates. RESULTS: Among 1490 patients (80% Swiss, 56% male, age 75 ± 13 years), 621 experienced the primary outcome at 1 year. Compared to those with stable normal/low systolic blood pressure, patients with decreasing systolic blood pressure had a significantly lower risk of the primary outcome (adjusted HR: 0.81; 95% CI: 0.66–0.99; p = 0.040), with no significant differences for the other systolic blood pressure trajectories. Results remained consistent regardless of sex, age and left ventricular ejection fraction (Pinteraction for all >0.05). CONCLUSION: In this real-world, multinational cohort of 1490 acute heart failure patients, in-hospital decline in systolic blood pressure was independently associated with improved outcomes in those with an elevated systolic blood pressure at admission.